Critical transition in critical zone of intensively managed landscapes. (June 2018) - Kumar, Praveen; Le, Phong V.V.; Papanicolaou, A.N. Thanos; Rhoads, Bruce L.; Anders, Alison M.; Stumpf, Andrew; Wilson, Christopher G.; Bettis, E. Arthur; Blair, Neal; Ward, Adam S.; Filley, Timothy; Lin, Henry; et al.
Highlights: Industrial agriculture has resulted in critical transition in landscape functioning. Landscape has been converted from transformation- to transport-dominated system. Human impacts have altered the rates of reaction and transport across the landscape. Emergent dynamics is restructuring the landscape heterogeneity. Abstract: Expansion and intensification of managed landscapes for agriculture have resulted in severe unintended global impacts, including degradation of arable land and eutrophication of receiving water bodies. Modern agricultural practices rely on significant direct and indirect human energy inputs through farm machinery and chemical use, respectively, which have created imbalances between increased rates of biogeochemical processes related to production and background rates of natural processes. We articulate how these imbalances have cascaded through the deep inter-dependencies between carbon, soil, water, nutrient and ecological processes, resulting in a critical transition of the critical zone and creating emergent inter-dependencies and co-evolutionary trajectories. Understanding of these novel organizations and function of the critical zone is vital for developing sustainable agricultural practices and environmental stewardship.